2019
DOI: 10.1111/imj.14222
|View full text |Cite
|
Sign up to set email alerts
|

Burden of skin disease in two remote primary healthcare centres in northern and central Australia

Abstract: The burden of skin infections across all age groups in remote Australian Indigenous communities is currently unknown. In a retrospective audit of 439 residents from two remote communities presenting to health clinics, skin conditions were the most common reason for presentation (1603/7392, 22%) and 330/439 (75%) residents presented at least once with a skin infection. Skin infections are an under-appreciated and dominant reason for presentation to primary healthcare centres in these indigenous communities and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…Of critical concern, CA-MRSA was documented in over 40% of SSTIs, either by wound culture or presumed by previous colonization. Although research around skin infections in Indigenous communities is limited, this high burden of infection aligns with the current literature; in Australia, researchers have found that 75% of residents from two remote Australian Indigenous communities visited a primary healthcare centre with a skin infection at least once in a year, and skin infections were the dominant reason for visiting a primary healthcare centres in Indigenous communities [19]. They also found MRSA rates around 50% in the north (of Australia) [20], and highlighted the high burden of skin infections in Indigenous communities in Australia.…”
Section: Discussionsupporting
confidence: 64%
“…Of critical concern, CA-MRSA was documented in over 40% of SSTIs, either by wound culture or presumed by previous colonization. Although research around skin infections in Indigenous communities is limited, this high burden of infection aligns with the current literature; in Australia, researchers have found that 75% of residents from two remote Australian Indigenous communities visited a primary healthcare centre with a skin infection at least once in a year, and skin infections were the dominant reason for visiting a primary healthcare centres in Indigenous communities [19]. They also found MRSA rates around 50% in the north (of Australia) [20], and highlighted the high burden of skin infections in Indigenous communities in Australia.…”
Section: Discussionsupporting
confidence: 64%
“…Many clinics have treatment guideline informed formularies, ensuring a streamlined supply of antimicrobials. Widespread use of electronic medical records provides the capacity for high level understanding of prescribing and dispensing …”
Section: The Way Forwardmentioning
confidence: 99%
“…At any one time, 45% of children will have impetigo, 7 up to 80% of infants aged under 1 year will be hospitalised for a lower respiratory tract infection, 8 66% of children will present with otitis media before 5 years of age, 9 and 75% of all community members present with skin and soft tissue infections each year. 10 In adults, skin and sexually transmitted infections remain challenging, while sepsis rates resulting in hospitalisation and intensive care admission are fourfold higher in Indigenous than in non-Indigenous Australians in northern Australia. 11 Due to this burden, high frequency appropriate antimicrobial use is required: 95% of children receive at least one antibiotic prescription and 47% receive at least six antibiotic prescriptions by their first birthday.…”
Section: Heavy Burden Of Infections and Antimicrobial Usementioning
confidence: 99%
See 1 more Smart Citation
“…The data demonstrated that SSTIs were the most frequent indications for antimicrobial use in all three regions. 15,37 This finding highlights the difference in morbidity profiles and patterns of antimicrobial use between remote and urban communities, as upper respiratory tract infections are typically the most common reason for an antimicrobial prescription in urban areas. 38 The appropriateness of antimicrobial use was high compared with urban GP settings around Australia.…”
Section: Discussionmentioning
confidence: 87%